2004
DOI: 10.1158/1078-0432.ccr-04-0443
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Collagen XVIII Is Associated with Poor Outcome and Elevated Levels of Circulating Serum Endostatin in Non–Small Cell Lung Cancer

Abstract: Purpose: The aim of this study was to determine whether collagen XVIII expression is correlated with circulating serum endostatin and whether this has any prognostic value in patients with non-small cell lung cancer (NSCLC).Experimental Design: Serum endostatin levels were measured quantitatively by a competitive enzyme immunoassay, and collagen XVIII expression in tumor tissue was investigated with an immunohistochemical method in a series of 94 patients who underwent surgery for NSCLC.Results: Sixty cases (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Although the correlation index was relatively weaker, we found that a stronger endostatin expression correlates with higher serum levels of endostatin, suggesting that serum endostatin originated partially from tumor cells. Our findings are in concordance with the result found in NSCLC by Iizasa et al (34). However, in 12 patient-matched cases, serum endostatin concentration manifested no significant association with immunohistochemical staining, although this maybe due to the small sample size (11).…”
Section: Discussionsupporting
confidence: 92%
“…Although the correlation index was relatively weaker, we found that a stronger endostatin expression correlates with higher serum levels of endostatin, suggesting that serum endostatin originated partially from tumor cells. Our findings are in concordance with the result found in NSCLC by Iizasa et al (34). However, in 12 patient-matched cases, serum endostatin concentration manifested no significant association with immunohistochemical staining, although this maybe due to the small sample size (11).…”
Section: Discussionsupporting
confidence: 92%
“…With regard to endostatin expression in lung cancer, the presence of its precursor, collagen XVIII, in lung cancer cells was confirmed previously [17]. Notably, some investigators from the same institute reported previously that its expression in lung cancer tissue was associated with tumor progression and poor outcomes in assessment of patients at various stages [17,18].…”
Section: Commentsmentioning
confidence: 53%
“…Endostatin is present at detectable levels in the serum of normal individuals (Feldman et al, 2002;IIzasa et al, 2004) and canstatin/arresten has been isolated from human placenta, suggesting physiological function. Further indirect evidence is provided by the study of mouse strains with null mutations in the parental ECM molecule and rare single gene disorders in humans (see Table 2).…”
Section: A Physiological Role?mentioning
confidence: 99%
“…It is unclear whether these elevated endostatin levels are due to direct intratumoral production or a coordinated 'host' response to proangiogenic stimuli, in particular VEGF produced by the cancer (Feldman et al, 2002;Glenjen et al, 2002;Iizasa et al, 2004). What such findings do suggest however is that if this endogenous endostatin is in an active form, further increasing serum endostatin levels to pharmacological levels may not have a significant additional antiangiogenic effect as it is possible that in clinically manifest tumours, once the angiogenic switch has been tripped, raising the levels of endogenous antiangiogenic agents further is not very effective in resetting this.…”
Section: Targeting An Already Overloaded Systemmentioning
confidence: 99%